Impact of type 2 diabetes on hospitalization and mortality in people with malignancy. Issue 2 (11th October 2019) - Kiburg, K. V.; Ward, G. M.; Vogrin, S.; Steele, K.; Mulrooney, E.; Loh, M.; McLachlan, S. A.; Sundararajan, V.; MacIsaac, R. J.
Abstract: Aim: To compare the characteristics of and outcomes for people with malignancies with and without a co‐diagnosis of diabetes. Methods: Emergency department and hospital discharge data from a single centre for the period between 1 January 2015 and 31 December 2017 were used to identify people with a diagnosis of a malignancy and diabetes. Multivariate Cox regression models were used to estimate the effect of diabetes on all‐cause mortality. A truncated negative binomial regression model was used to assess the impact of diabetes on length of hospital inpatient stay. Prentice–Williams–Peterson total time models were used to assess the effect of diabetes on number of emergency department re‐presentations and inpatient re‐admissions. Results: Of 7004 people identified with malignancies, 1195 (17.1%) were also diagnosed with diabetes. A diagnosis of diabetes was associated with a greater number of inpatient re‐admissions [adjusted hazard ratio 1.13 (95% CI 1.03, 1.24)], a greater number of emergency department re‐presentations [adjusted hazard ratio 1.13 (95% CI 1.05, 1.22)] and longer length of stay [adjusted incidence rate ratio 1.14 (95% CI 1.04, 1.25)]. A co‐diagnosis of diabetes was also associated with a 48% increased risk of all‐cause mortality [adjusted hazard ratio 1.48 (95% CI 1.22–1.76)]. Conclusions: People with malignancies and diabetes had significantly more emergency department presentations, more inpatient admissions, longer length of hospital stay and higher rates of all‐cause mortality compared to people with a malignancy without diabetes. What's new?: It has been shown that a diagnosis of diabetes is associated with an increased risk of the development and progression of malignancies, and of mortality in people with malignancies, a number of suggested explanations for which include hyperinsulinaemia and hyperglycaemia. The findings of the present study highlight the increased risk of emergency department presentatios, inpatient admission, longer length of hospital stay and all‐cause mortality associated with a diagnosis of diabetes and malignancy. This work emphasizes the importance of avoiding diabetes, and highlights that people who have already developed diabetes and have a co‐diagnosis of a malignancy represent a high‐risk group that may benefit from additional treatment strategies.